Toward a test of angular-momentum coherence in a twin-atom interferometer. (18th June 2015) - de Carvalho, Carlos R.; Jalbert, Ginette; Impens, François; Robert, J.; Medina, Aline; Zappa, F.; de Castro Faria, N. V.
Abstract: We present a scheme well suited to investigate quantitatively the angular-momentum coherence of molecular fragments. Assuming that the dissociated molecule has a null total angular-momentum, we investigate the propagation of the corresponding atomic fragments in the apparatus. We show that the envisioned interferometer enables one to distinguish unambiguously a spin-coherent from a spin-incoherent dissociation, as well as to estimate the purity of the angular-momentum density matrix associated with the fragments. This setup, which may be seen as an atomic analogue of a twin-photon interferometer, can be used to investigate the suitability of molecule dissociation processes —such as the metastable hydrogen atoms H(2 2 S )-H(2 2 S ) dissociation— for coherent twin-atom optics.